2022
DOI: 10.3389/fsurg.2021.801911
|View full text |Cite
|
Sign up to set email alerts
|

Similar Efficacy of Arthroscopy and Arthrotomy in Infection Eradication in the Treatment of Septic Knee: A Systematic Review and Meta-Analysis

Abstract: Aim: To compare the arthroscopy vs. arthrotomy for the treatment of native knee septic arthritis.Methods: Electronic databases of PubMed, Embase and Cochrane Library were searched for eligible studies. Retrospective comparative studies comparing arthroscopy or arthrotomy for patients with septic arthritis of the native knee were eligible for this review. The primary outcome was recurrence of infection after first procedure. The secondary outcomes included hospital length of stay, operative time, range of motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…Therefore, the overall conclusion of this review is that neither arthroscopy nor arthrotomy showed superiority in reducing reoperation rate. This aligns with findings of previous reviews of this subject [ 11 , 28 , 38 ] with the exception of Acosta‐Olivo et al [ 2 ] who found that arthroscopic washout was superior.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the overall conclusion of this review is that neither arthroscopy nor arthrotomy showed superiority in reducing reoperation rate. This aligns with findings of previous reviews of this subject [ 11 , 28 , 38 ] with the exception of Acosta‐Olivo et al [ 2 ] who found that arthroscopic washout was superior.…”
Section: Discussionsupporting
confidence: 91%
“…The surgical washout of a joint can either take the form of arthroscopy or arthrotomy. Contradictory conclusions have been drawn from prior reviews regarding the efficacy of arthroscopy in eradicating infection [ 2 , 28 ]. There is also no consensus on the functional and clinical results associated with both procedures for various patient cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…The present study represents the rst systematic review focusing primarily on function following AW and OW. Our ndings agree with PROMs and ROM described in reviews by Panjwani (13) and Liang (12) , respectively. This was predictable, as we retrieved just one additional study reporting PROMs (26) , and none further reporting ROM.…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…However, the con dence intervals were imprecise suggesting heterogeneity, so the results should be interpreted cautiously. In keeping with our ndings, Liang (12) showed a possible trend for lower rates of reinfection following AW (OR = 0.85; p = 0.44), whilst Panjwani (13) reported substantially reduced risk of re-operation (RR = 0.69; p = 0.0006). Both these reviews included additional studies in their pooled analyses which were excluded from the present study due to omission of PROMs (35)(36)(37)(38)(39) .…”
Section: Comparison With Other Studiessupporting
confidence: 89%
See 1 more Smart Citation